Pemanfaatan serat alam kulit terap sebagai bahan kombinasi pembuatan winglet sepeda motor - Rianto, Ari; Anjiu, Leo Dedy; Suhendra, Suhendra (TURBO [Tulisan Riset Berbasis Online], 2020)
The development of new natural fiber material as a composite reinforcing material needs to be continued. The use of natural fibers developed in this study was obtained from applied bark. The applied skin fiber is chosen as a composite reinforcing material because it has strong characteristics when pulled. This study was conducted to determine the impact strength of a combination of the arrangement of the composite layer of applied fiber and glass fiber with a polyester resin matrix in the manufacture of motorcycle winglets. The making of composite specimens was carried out by hand lay-up and pressing techniques. composite specimens tested consisted of composite A (100% fiberglass), composite B (100% applied fiber), composite C (fiberglass, applied fiber, fiberglass), and composite D (applied fiber, fiberglass, applied fiber). The treatment of the applied fiber was carried out by soaking 5% NaOH for 2 hours. Impact test specimens and procedures refer to the ASTM D256-00 standard. The results of the study obtained that the material recommended in the manufacture of motorcycle winglets is composite C, which is a combination of fiberglass, applied fiber, fiberglass. The results of the C composite impact strength testing were obtained at 2.6581 J / mm2. The impact strength of composite C increased by 79% compared to the impact strength of composite B using pure applied fiber (100% applied fiber). The large void tendency in natural fiber composites using the hand lay-up method reduces the impact strength so that fiberglass is more dominant as a determinant of the impact strength increase.Keywords : Applied fiber, impact test, winglet.